Implementasi Strategi Pemerintah Daerah Dalam Mewujudkan Pariwisata Berbasis Budaya Terkemuka (Studi pada Dinas Pariwisata Daerah Istimewa Yogyakarta) - Eva Rusdiananingtyas (Jurnal Administrasi Publik, 2015)
Abstract: The Implementation of Local Government Strategy in Creating The Notable Culture-Based Tourism (A Study in Tourism Department of Daerah Istimewa Yogyakarta). Daerah Istimewa Yogyakarta (DIY) has wealth and potency of tourism such as culture inheritance and the beauty of nature that can be featured to be a tourism objective both in Indonesia and foreign countries. The tourism sector becomes excellent sector in economy of DIY, however the tourism development of DIY also produces various challenges and constraints so that the effort of the tourism development need to be done seriously and by using an appropriate strategy. From the result of the research can be known that there are three strategies used by DIY Tourism Department that are the strategy in increasing the quality and quantity of tourism destination, the strategy in creating effective and efficient marketing, and also the strategy to optimize the expansion of cooperation. The strategy implementations are explained into three primary programs that are destination development program, marketing development program, and cooperation development program. The effectiveness of the strategy implementation can be seen from the reachable target in settled indicators. In the process of implementation this strategy there are proponent factors such as estimate availability, tourism potency, infrastructure availability, the role of society and social-safety condition. Meanwhile, the obstacle factors are apparatus sources that are inadequate, and also the cooperation between stakeholders that still cannot be synergic.   Keyword: strategy implementation, tourism development, culture of tourism Abstrak: . Daerah Istimewa Yogyakarta (DIY) memiliki kekayaan dan potensi pariwisata berupa warisan budaya maupun keindahan alam yang dapat diunggulkan menjadi tujuan wisata terkemuka baik di Indonesia maupun Mancanegara. Sektor pariwisata menjadi sektor unggulan perekonomian DIY, namun demikian pembangunan pariwisata DIY juga memunculkan berbagai tantangan dan kendala, sehingga upaya pengembangan pariwisata perlu dilakukan dengan serius dan strategi yang tepat. Dari hasil penelitian dapat diketahui bahwa terdapat tiga strategi yang diterapkan Dinas Pariwisata DIY yaitu strategi meningkatkan kualitas dan kuantitas destinasi pariwisata, strategi mewujudkan pemasaran yang efektif dan efisien, serta strategi mengoptimalkan perluasan jaringan kerjasama. Implementasi strategi dijabarkan dalam tiga program utama yaitu program pengembangan destinasi, program pengembangan pemasaran, dan program pengembangan kemitraan. Efektivitas implementasi strategi dapat dilihat dari tercapainya target dalam indikator yang telah ditetapkan. Dalam pelaksanaannya terdapat faktor pendukung yang meliputi ketersediaan anggaran, potensi pariwisata, ketersediaan sarana prasarana, peran serta masyarakat dan kondisi sosial-keamanan. Sedangkan faktor penghambatnya adalah sumber daya aparatur yang kurang memadai, serta kerjasama antar stakeholders yang  belum sinergis.   Kata Kunci: implementasi strategi, pengembangan pariwisata, wisata budaya